ANALISIS KESALAHAN SISWA KELAS IX SMP DALAM MENYELESAIKAN SOAL PADA MATERI LINGKARAN - Wina Nur Alifah Suherman; Nelly Fitriani; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research aims to analyze in order to find out the mistakes of Asyifa 44 Junior High School students in solving problems on circle material. Has a qualitative descriptive method. The data taken in the study were the results of the answers of 20 junior high school students in class IX of SMP. The instrument used includes a test instrument in the form of circular material questions as many as 6 items. Processing in this study using triangulation. Some of the mistakes made by students when solving circle material problems include: (1) mistakes in distinguishing several elements of the circle, (2) completing half of the answers, (3) not using long units, (4) unable to prove the relationship between the perimeter angle with the center angle, (5) have not been able to find a number pattern, (6) are wrong in comparing images, (7) cannot conclude a solution. Problems with the largest percentage were number 1 at 90%, and questions with the lowest percentage were number 3 at 20%.